2020
DOI: 10.1016/j.immuni.2020.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Proteomics Identify Biomarkers and Pathogenesis of COVID-19

Abstract: The COVID-19 pandemic is a global public health crisis. However, little is known about the pathogenesis and biomarkers of COVID-19. Herein, we profiled host responses to COVID-19 by performing plasma proteomics of a cohort of COVID-19 patients including non-survivors and survivors recovered from mild or severe symptoms, and uncovered numerous COVID-19-associated alterations of plasma proteins. We developed a machine learning-based pipeline to identify 11 proteins as biomarkers and a set of biomarker combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
273
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(322 citation statements)
references
References 63 publications
(63 reference statements)
26
273
0
Order By: Relevance
“…Several recent investigations have identified protein biomarkers and clinical parameters that classify COVID-19 patients according to disease severity [7][8][9][10][11][12][13][14][15] . To identify i) which of these markers and parameters correlate with each other by being attributed to a common biological or physiological response, and ii) which markers predict outcome, we longitudinally phenotyped 139 individuals admitted at Charité University Hospital, Berlin, Germany, between March 01, 2020 and June 30, 2020 due to PCR confirmed SARS-CoV-2 infection (Supp.…”
Section: Covariation Of Clinical Diagnostic Parameters and The Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent investigations have identified protein biomarkers and clinical parameters that classify COVID-19 patients according to disease severity [7][8][9][10][11][12][13][14][15] . To identify i) which of these markers and parameters correlate with each other by being attributed to a common biological or physiological response, and ii) which markers predict outcome, we longitudinally phenotyped 139 individuals admitted at Charité University Hospital, Berlin, Germany, between March 01, 2020 and June 30, 2020 due to PCR confirmed SARS-CoV-2 infection (Supp.…”
Section: Covariation Of Clinical Diagnostic Parameters and The Plasmamentioning
confidence: 99%
“…A number of biomarkers that classify COVID-19 severity have recently been described, based on clinical chemistry, enzyme activities, immunoprofiling, single cell sequencing, proteomics, and metabolomics [7][8][9][10][11][12][13][14][15] . These severity classifiers characterize COVID-19 pathology and host responses mainly in blood, serum, plasma or immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…Host proteome analysis using blood has been instrumental in gauging the response of the host as well as identifying classifiers of severity that will be clinically useful. 61 , 108 …”
Section: Resultsmentioning
confidence: 99%
“…For the 46 protein biomarkers described by Shu et al [1], 34 were available for measurement in the Somalogic platform: 4 of 18 were found to differ in PCOS for platelet…”
Section: To the Editormentioning
confidence: 99%